2022
DOI: 10.1021/acs.inorgchem.2c02545
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Properties of Volatile Lanthanide Dialkyltriazenides

Abstract: Several dialkyltriazenide complexes of the lanthanide elements neodymium, europium, and erbium have been prepared; these include the homoleptic complex Er(Bu t N 3 Bu t ) 3 , the tetrahydrofuran monoadducts Ln(Bu t N 3 Bu t ) 3 (THF) where Ln = Nd or Eu, and the lithium salts [Li(THF)][Ln(MeN 3 Bu t ) 4 ] where Ln = Eu or Er. Crystal structures, nuclear magnetic resonance data, and infrared data are reported for all complexes. The di-tert-butyltriazenide complexes are thermally stable, sublime at reasonably lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…A triazenido metal complex can be synthesized in different ways, either by deprotonation of a triazene, [3,4] by salt‐metathesis reaction with a triazenido anion [4] or via insertion of an organic azide into a metal‐alkyl [8] or metal‐hydride [9] bond. As demonstrated by very recent works on main group elements, [10] lanthanides [11] and late transition metal complexes, [12] triazenido ligands are an emerging class of ligands and of current interest. Regarding group IV metals, an early example of a triazenido complex was reported by Hillhouse et al., specifically the Cp* 2 HfH(NHNNPh) complex via insertion of phenyl azide into the Hf−H bond [9] .…”
Section: Introductionmentioning
confidence: 99%
“…A triazenido metal complex can be synthesized in different ways, either by deprotonation of a triazene, [3,4] by salt‐metathesis reaction with a triazenido anion [4] or via insertion of an organic azide into a metal‐alkyl [8] or metal‐hydride [9] bond. As demonstrated by very recent works on main group elements, [10] lanthanides [11] and late transition metal complexes, [12] triazenido ligands are an emerging class of ligands and of current interest. Regarding group IV metals, an early example of a triazenido complex was reported by Hillhouse et al., specifically the Cp* 2 HfH(NHNNPh) complex via insertion of phenyl azide into the Hf−H bond [9] .…”
Section: Introductionmentioning
confidence: 99%
“…24,26 During our studies, volatile and thermally stable lanthanide dialkyltriazenides have also been reported. 30 With the success of the triazenide ligand to produce volatile and thermally stable metal compounds, we decided to investigate its reactivity with divalent Zn. Herein, we report the synthesis, structure, and thermal properties of a Zn(II) triazenide and its reactivity with sterically bulky thiols that mimic a ZnS surface.…”
Section: Introductionmentioning
confidence: 99%